Store Atmosphere and Quality of Personal to Predicate Repatronage Intentions at Local Convenience Stores: The Role of Customer Satisfaction as a Mediation Variable - Yosua Tantri Saman; Keni Keni; Rajendran Muthuveloo (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to empirically test store atmosphere, quality of personal, and customer satisfaction as predictors of repatronage intentions at local convenience stores. The online questionnaire was distributed using Google Forms with a 5-point Likert scale for each indicator. The number of samples is 170 respondents. All data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) method, using SmartPLS 3.0 software. The results of this study indicate that store atmosphere, quality of personal, and customer satisfaction can positively predict repatronage intentions. The results show that the company can determine the right operational strategy by taking into account the factors that can increase repatronage intentions so that they can compete with competitors.